CaMKII in sinoatrial node physiology and dysfunction - Wu, Yuejin; Anderson, Mark E. (Frontiers in Pharmacology, 2014)
The calcium and calmodulin dependent protein kinase II (CaMKII) is present in sinoatrial node (SAN) pacemaker cells and is required for physiological “fight or flight” SAN beating rate responses. Inhibition of CaMKII in SAN does not affect baseline heart rate, but reduces heart rate increases in response to physiological stress. CaMKII senses intracellular calcium (Ca2+) changes, oxidation status and hyperglycemia to phosphorylate substrates that regulate Ca2+-sensitive proteins, such as L-type Ca2+ channels, phospholamban (PLN), and cardiac ryanodine receptors (RyR2). All of these substrates are involved in the SAN pacemaking mechanism. Excessive CaMKII activity, as occurs under pathological conditions such as heart failure, ischemia and diabetes, can promote intracellular Ca2+ overload and reactive oxygen species (ROS) production. Oxidation of CaMKII (ox-CaMKII) locks CaMKII into a constitutively active configuration that contributes to SAN cell apoptosis and fibrosis. This ox-CaMKII-mediated loss of functional SAN cells contributes to sinoatrial node dysfunction (SND) and sudden death. Thus, CaMKII has emerged as a central regulator of physiological SAN responses and a key determinant of SND.